TRANSLATIONS OF ALISHER NAVOIS WORKS INTO KARAKALPAK LANGUAGE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Today, serious and complex changes are taking place in all spheres of society. In particular, a number of scientific works on translation and artistic, scientific changes are being made on artistic creation. Organizing and analyzing the spiritual values of every nation, wherever humanity is, the sense of artistic mastery is inextricably linked with this basic art of translation.